Key Issues in Critical Care Medicine Include ECPR and IV Fluid Management - Kuznar, Wayne (MD Conference Express, 2014)
Key issues in critical care for the acute care cardiologist were addressed by a panel of experts. Specific topics include the Berlin definition of acute respiratory distress syndrome, merging applications for extracorporeal support, intravenous fluid managementa, s well as emerging pathogens in sepsis.